Assessing Tree Biomass and Carbon Stock Differences Between Sacred Groves in Kathmandu District, Nepal (The Harvest, 2026)
Sacred groves, which are maintained over a long period of cultural and religious practices, are important ecological reserves that play a great role in conserving biodiversity and managing climate change. The objective of this study is to measure and compare the biomass and carbon stock in two sacred groves in Kathmandu District Swayambhu Sacred Grove (SSG) and Dakshinkali Sacred Grove (DSG) to determine the relative contribution of the two groves in the local carbon sequestration. Systematic random sampling was done to determine 89 circular plots of area 10 m radius with the help of Google Earth Image and 77 of the accessible plots were sampled (30 in SSG and 47 in DSG). Systematic records were made on diameter of tree at breast height (DBH), tree height, and species identity. Overground biomass was determined as the Chave et al. (2005) allometric model, whereas the belowground biomass was estimated by using a standard root to shoot ratio. The total biomass was then divided into carbon stock with the IPCC carbon fraction of 0.47. Species-wise Carbon contribution was conducted to find out structural and ecological disparities between the groves. It is found in the results that there are evident differences in biomass accumulation and carbon storage between the two sites. Compared to DSG, SSG had significantly greater above-ground biomass (201.7 t/ha) and below-ground biomass (40.3 t/ha). Total carbon stock was also considerably high in SSG (113.76 ± 1.687 t/ha) compared to DSG (79.87 ± 1.113 t/ha) and statistical analysis showed that there was a significant difference between them (p = 0.021). Species composition analysis also indicated that SSG was even and rich in carbon with Schima wallichii as the dominant one, and DSG had Pinus roxburghii and Alnus nepalensis as the best dominating species. All in all, the paper emphasizes that SSG is a more developed, structurally further and efficient carbon reservoir in comparison with DSG that depicts less carbon storage since the forest structure is more homogenous.